The Importance of Increasing Awareness of Business Permits and Technological Transformation in Empowering MSMEs: Bouncing Back Post COVID-19 Pandemic - Wijaya, Sonny; Lilla Puji Lestari; Ahmad Heru Romadhon; M Choifin (Universitas Nahdlatul Ulama Surabaya, 2023)
The COVID-19 pandemic has had a significant impact on Micro, Small, and Medium Enterprises (MSMEs) worldwide, including in the village where the author conducted Community Service (Kuliah Kerja Nyata – KKN), in Sawocangkring Village, Cangkring Hamlet, Wonoayu, Sidoarjo, East Java, Indonesia from August 1st to 31st, 2023. During this community service activity, many local MSMEs experienced setbacks and even had to close down when the COVID-19 pandemic hit the country. To ensure the sustainability and recovery of MSMEs post COVID-19 pandemic, it is important to raise awareness of the role of business permits and technological transformation in empowering MSMEs. However, there is still a lack of knowledge and understanding among MSME owners regarding the importance of these two aspects. This community service activity was conducted using a qualitative approach with a descriptive method, involving observation and interviews. Additionally, primary data was collected through pre and post activity surveys in the form of questionnaires administered to MSMEs owners. In this case, as a pilot project for community service activities, the author focused only on selecting 2 leading MSMEs as partners for this community service activity. The results of this community service activity related to business permits include socialization and assistance in obtaining the Business Identification Number (Nomor Induk Berusaha - NIB). As for technological transformation, socialization and assistance were provided in creating websites for MSMEs, Google Map location services, and e-commerce platforms such as Shopee and Tokopedia. In the context of post COVID-19 pandemic MSME recovery, increasing awareness of the importance of business permits and technological transformation plays a crucial role in empowering MSMEs. By enhancing the knowledge and understanding of MSMEs owners regarding legitimate business permit procedures and the benefits of technological transformation, MSMEs can gain better access to markets, financing, and resources needed to recover and grow their businesses.